2014
DOI: 10.2174/1573413710666140701184953
|View full text |Cite
|
Sign up to set email alerts
|

Novel Iron-oxide Catalyzed CNT Formation on Semiconductor Silicon Nanowire

Abstract: An aqueous ferric nitrate nonahydrate (Fe(NO3)3.9H2O) and magnesium oxide (MgO) were mixed and deposited on silicon nanowires (SiNWs), the carbon nanotubes (CNTs) formed by the concentration of Fe3O4/MgO catalysts with the mole ratio set at 0.15:9.85 and 600°C had diameter between 15.23 to 90nm with high-density distribution of CNT while those with the mole ratio set at 0.45:9.55 and 730°C had diameter of 100 to 230nm. The UV/Vis/NIR and FT-IR spectroscopes clearly confirmed the presence of the silicon-CNTs hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Iron oxides are among the most studied materials due to their fundamental properties and potential applications. 12 Mohaparta et al 13 in 2015 reported enhanced MRI contrast of iron oxide nanorods that was attributed to the higher surface area and anisotropic morphology. 3 Due to their nano-scale one-dimensional structure, nanowire shape shows unique mechanical, electrical, magnetic properties having potential applications for various mesoscopic electronic and optical devices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Iron oxides are among the most studied materials due to their fundamental properties and potential applications. 12 Mohaparta et al 13 in 2015 reported enhanced MRI contrast of iron oxide nanorods that was attributed to the higher surface area and anisotropic morphology. 3 Due to their nano-scale one-dimensional structure, nanowire shape shows unique mechanical, electrical, magnetic properties having potential applications for various mesoscopic electronic and optical devices.…”
Section: Introductionmentioning
confidence: 99%
“…7 The research for the production of iron oxide nanowires has both theoretical and practical interest because these could be useful in a variety of elds, such as in medicine, 8 as biological and magnetic contrast, 9 as starting material for the preparation of photoconductors, 10 in biology, 11 in catalysis of carbon nanotube growth. 12 Mohaparta et al 13 in 2015 reported enhanced MRI contrast of iron oxide nanorods that was attributed to the higher surface area and anisotropic morphology. The higher surface area induces a stronger magnetic eld perturbation over a larger volume more effectively for the outer sphere protons.…”
Section: Introductionmentioning
confidence: 99%